O esquete no ensino de geografia: proposição didática no Colégio Estadual do Campo Aprendendo com a Terra e com a Vida - Peluso, Daiane (2019)
In developing the research, the practice of sketches was experienced as a methodology in the teaching and learning of geography. When adopted in teaching, it allows the understanding of reality through the act of “staging”. The debate began with the theater and its history, was focused on the analysis of its configurations along the human trajectory, in the main theories and its authors were highlighted, bringing together the essential theatrical forms existing today. During the study, the debate permeated the theater developed on Brazilian soils, followed by the analysis of the theater performed in the state of Paraná and concludes with the concept of Esquete and the association with the teaching of geography. The Education of the Field was worked on, the main points of its historical trajectory were questioned, it starts to analyze the locus of the research that ends with the interviews of educators linked in this perspective and contribute to the enrichment of the study, reporting their stories and understandings about education in which students are historical subjects. Subsequently, the development of the sketches is carried out at the State College of the Field Learning with the Earth and Life, in the municipality of Cascavel-PR., with the time frame from 2017 to 2019, highlights and illustrates the various constitutive stages of the achievement Skits, which ends with the comparison of data between the initial and final diagnoses of the participating students.